Intranasal fluticasone propionate does not prevent acute otitis media during viral upper respiratory infection in children()() - Ruohola, Aino (J Allergy Clin Immunol, 2000)
Background: Acute otitis media (AOM) is the most common complication of a viral upper respiratory infection (URI) in children. The virus-induced host inflammatory response in the nasopharynx plays a key role in the pathogenesis of AOM. Suppression of this inflammatory process might prevent the development of AOM as a complication. Objective: We sought to assess the effect of intranasally administered fluticasone propionate on prevention of AOM during a viral respiratory infection. Methods: A total of 210 children (mean age, 2.1 years; range, 0.7-3.9 years) with normal middle ear status and URI of 48 hours’ duration or less were randomly allocated to receive either fluticasone (100 μg twice daily) or placebo for 7 days. The specific viral cause of the infection was determined from nasopharyngeal aspirates obtained at the first visit. The children were re-examined at the end of the 7-day medication period. Results: In the fluticasone group AOM developed in 40 (38.1%) of 105 children compared with 29 (28.2%) of 103 children receiving placebo (P = .13). The viral cause of the respiratory infection was determined in 167 (86.1%) of 194 children from whom a nasopharyngeal aspirate was obtained. In children with rhinovirus infection, AOM developed significantly more often in the fluticasone group (45.7%) than in the placebo group (14.7%, P = .005). Conclusion: Intranasally administered fluticasone does not prevent the development of AOM during URI but may increase the incidence of AOM during rhinovirus infection. (J Allergy Clin Immunol 2000;106:467-71.)